THE INFLUENCE OF SERVICE QUALITY TO CUSTOMER SATISFACTION IN PDAM KUPANG’S SERVICE COUNTERS - Antonio E.L. Nyoko; Ronald P.C. Fanggidae; Ni Putu Nursiani (Universitas Nusa Cendana, 2016)
Service Quality is very important factor especially for enterprises that engaged in the services sector.Therefore, PDAM Kupang prioritizes the service quality for the sake of customers satisfaction, bytrying to improve the quality of service which is expected to be a positive effect towards customersatisfaction. The purpose of this research is to explain the influence of the counters service quality tocustomer satisfaction in PDAM Kupang’s service counters. The result of the regression, the ServiceQuality influence positively towards Customer Satisfaction (β = 0,231). The variable of ServiceQuality has contribution of 53.4% to Customer Satisfaction variable (R2 = 0.534) and the restinfluenced by other variables. Based on a comparison between the value of tcount and ttable (n-2) at the95% level of confidence, it can be drawn the conclusion that the variable of Service Quality influencesignificantly to variable of Customer Satisfaction. It means that the service quality in PDAMKupang’s service counters have influence to its costumers satisfaction.Keywords : Customer Satisfaction, Customer Services, Service Quality